Meningkatkan Aktivitas Dan Hasil Belajar Muatan PPKN Menggunakan Model PBL, Discovery Learning, Dan Talking Stick Pada Siswa Kelas V SDN Antasan Kecil Timur 3 Banjarmasin - Erisa Winda Bestari; Amberansyah Amberansyah (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2023)
The problem of this research is the lack of understanding of the material and student involvement and learning outcomes that have not yet reached the KKM. This study aims to increase student learning activities and outcomes in civic education learning in class V SDN Antasan Kecil Timur 3 Banjarmasin. This study used a qualitative research approach with the type of Classroom Action Research (CAR), which was conducted in three meetings. The research setting was fifth grade students at SDN Antasan Kecil Timur 3 Banjarmasin for the 2022/2023 academic year, with a total of 23 students consisting of 12 male students and 11 female students. The results showed that teacher activity at meetings 1 to 3 increased from a score of 19 to 28. Student activity at meetings 1 to 3 increased from 43.4% to 82.6% (classical). Cognitive aspect learning outcomes at meetings 1 to 3 increased from 60.8% to 86.9% (classical). The learning outcomes of the affective domain of discipline at meetings 1 to 3 increased from 69.5% to 91.3% (classical), the affective domain of confidence at meetings 1 to 3 increased from 69.5% to 86.9% (classical) and learning the affective domain of the area of ​​responsibility at meetings 1 to 3 increased from 73.9% to 82.6% (classical). The results of learning the psychomotor aspects at meetings 1 to 3 increased from 47.8% to 82.6% (classical).